Real-World Safety Data of the Orphan Drug Onasemnogene Abeparvovec (Zolgensma®) for the SMA Rare Disease: A Pharmacovigilance Study Based on the EMA Adverse Event Reporting System - Rosanna Ruggiero; Nunzia Balzano; Maria Maddalena Nicoletti; Gabriella di Mauro; Federica Fraenza; Maria Rosaria Campitiello; Francesco Rossi; Annalisa Capuano (Pharmaceuticals, 2024)
The recent introduction of the innovative therapy, onasemnogene abeparvovec (Zolgensma®), has revolutionized the spinal muscular atrophy (SMA) therapeutic landscape. Although Zolgensma® therapy has proven to lead to functional improvements in SMA children, some gaps in its safety profile still need to be investigated. To better characterize the Zolgensma® safety profile, we conducted a retrospective observational study, analyzing all the Individual Case Safety Reports (ICSRs) referred to it and collected in the European pharmacovigilance database between 1 January 2019 and 22 September 2023. We found 661 ICSRs related to Zolgensma®, with a growing trend in the annual reporting. The majority of the reports were sent by healthcare professionals and referred to infant females. In more than 90% of the cases, Zolgensma® was the only reported suspected drug. Out of a total of 2744 reported ADRs, increased hepatic enzymes, pyrexia, vomiting, and thrombocytopenia were the most commonly reported adverse reactions. Of these adverse reactions (ADRs), 56.9% were serious, causing or prolonging the patient’s hospitalization. A total of 39 ICSRs related to cases with a fatal outcome. Alterations in the heart rhythm, acute hepatic failure, and hepatic cytolysis emerged among the cardiac and hepatic disorders, respectively.